2013
DOI: 10.1049/mnl.2013.0195
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical performance of TiO 2 /Au/carbon nanotubes composite interface for hydroquinone detection

Abstract: A novel nanocomposite was prepared by direct mixing of titania nanoparticles (nano-TiO 2) and gold nanoparticles (nano-Au)-modified carbon nanotubes (CNTs) in a solution of chitosan. The electrochemical performance of a TiO 2 /Au/CNT nanocomposite-modified electrode for hydroquinone detection was investigated. When measured at a scan rate of 50 mV s − 1 , the detected amount of hydroquinone at the TiO 2 / Au/CNT electrode varied linearly with hydroquinone concentration, for concentrations from 1 × 10 − 6 to 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, incorporating functional groups with CNTs increased the electrocatalytic activity. Li et al [104] . reported the preparation of a ternary nanocomposite of gold nanoparticles (AuNPs), titania nanoparticles (nano‐TiO 2 ), and CNTs to avoid entanglement and kink formation in CNT/nano‐TiO 2 nanocomposites.…”
Section: Selective Detection Of Hqmentioning
confidence: 99%
“…However, incorporating functional groups with CNTs increased the electrocatalytic activity. Li et al [104] . reported the preparation of a ternary nanocomposite of gold nanoparticles (AuNPs), titania nanoparticles (nano‐TiO 2 ), and CNTs to avoid entanglement and kink formation in CNT/nano‐TiO 2 nanocomposites.…”
Section: Selective Detection Of Hqmentioning
confidence: 99%
“…Enhancement of the electrochemical signal, due to introduction of selected nanostructures into electrochemical sensor system, was the goal of many studies described in the literature. [37][38][39][40][41] Introduction of graphene, gold and silica nanoparticles into one system have been investigated many times as well, especially toward catalytic applications. [42][43][44] Due to their properties they are also potentially attractive in the field of electrochemical sensing.…”
mentioning
confidence: 99%
“…26 Our preliminary studies include electro-catalysis of a ternary composition system based on Au/TiO 2 /CNT-we showed that the electrocatalytic activity was increased because of the synergistic action of Au, TiO 2 , and CNT. 9,27 In addition, if the sensing electrode is designed as a flexible and low-cost sensing paper, then the sensor has many potential applications including clinical diagnosis and food quality control. [28][29][30] Therefore, our research focuses on the development of a sensor based on the Au/TiO 2 /CNT nanocomposite for simultaneous electrochemical detection of AA, DA, UA, Trp, and nitrite.…”
mentioning
confidence: 99%